High xylooligosaccharides (XOS) production from pretreated kenaf stem by enzyme mixture hydrolysis - Wan Azelee, Nur Izyan; Md Jahim, Jamaliah; Ismail, Ahmad Fauzi; Mohamad Fuzi, Siti Fatimah Zaharah; A. Rahman, Roshanida; Md Illias, Rosli (Elsevier, 2016)
Advancement in industrial biotechnology offers potential opportunities for economic utilization of agro-industrial biomass such as kenaf (Hibiscus cannabinus) for the production of value-added products. This work was conducted to evaluate an enzymatic hydrolysis of kenaf stem (that has been pretreated) for xylooligosaccharides (XOS) production. Pretreated kenaf stems were subjected to two enzymatic hydrolysis approaches which are single xylanase (Xyn2) and a mixture of xylanase:arabinofuranosidase (Xyn2:AnabfA). Central Composite Design was used to optimize the enzymatic hydrolysis conditions on the pretreated kenaf stem to achieve maximum hemicellulose conversion. Under the optimized hydrolysis conditions, hemicellulose conversion (95.03%) with the highest XOS yield of 351.46 mg/g was achieved at 40 °C (pH 4.0) after 48 h incubation with Xyn2:AnabfA ratio of 400 U:10 U. Xylobiose (135.42 mg/g) is the main XOS product with xylotriose (102.04 mg/g) being the second highest. The high production of XOS yield from the pretreated kenaf stem demonstrated the biotechnological potential of the kenaf in the future.